Increased monocyte transcription of the proteinase 3 gene in small vessel vasculitis - Ohlsson, S (Blackwell Science Inc, 2005)
Proteinase 3 (PR3) is a pleiotropic and destructive serine protease and it is also a major target for autoantibodies in systemic small vessel vasculitis. We have shown recently that patients in stable remission have increased circulating levels of PR3, independent of autoantibody titre, inflammation, neutrophil degranulation and renal function. Here we explore the possibility of increased PR3 gene transcription. RNA was purified from peripheral blood monocytes from vasculitis patients and controls. Specific mRNA was measured by TaqMan real-time polymerase chain reaction (PCR). The monocyte-like cell lines THP-1 and U937 and human peripheral blod monocytes from healthy controls were stimulated with cytokines and lipopolysaccharide (LPS) for different time periods. PR3 protein was measured in plasma with enzyme-linked immunosorbent assay (ELISA). The median result for PR3 mRNA was 9·6 (1·8–680) for 22 patients, compared to 1 (0·1–2·8) for the 15 healthy controls. Elastase expression was also significantly increased, whereas myeloperoxidase and interleukin-8 were not. Stimulation of monocytes with tumour necrosis factor (TNF)-α, interferon (IFN)-γ or LPS did not result in any increase of PR3 or elastase transcription, whereas interleukin (IL)-8 transcription was increased 10-fold. Circulating monocytes from patients with systemic vasculitis display increased PR3 gene transcription compared to healthy controls and patients with sytemic lupus erythematosus (SLE). This may be important for the development of vasculitis. Our results do not favour a role for cytokines, antineutrophil cytoplasmic antibodies (ANCA) or immunosuppressive medication in the upregulation of PR3 transcription in vasculitis.